The Implementation of Genre-Based Teaching Method in Aerospace English Academic Writing Class (Global Journal of Human-Social Science, 2023)
Notwithstanding the voluminous literature devoted to academic writing especially using genre analysis more investigation needs to be done on academic writing pedagogy focusing on discipline-specific However English for Academic Purpose EAP has long been focusing on what students learn instead of how they learn In this regard this study provides an integrated genre-based academic writing teaching model by classroom observation and interview combining Rothery s 1994 genre-based teaching learning cycle Hommand 1994 s circular writing model with Swales 1990 move analysis to shed some light on aerospace English academic writing classroom setting This study also designs interviews to investigate the views of students toward genre-based teaching model and academic English writing Hopefully this integrated genre-based teaching model can develop students writing ability while improving their academic literacy
Keywords: genre-based teaching method; genre; academic writing; aerospace